MENGEMBANGKAN KEYBOARDING SKILLS BERBASIS PERMINTAAN INDUSTRI MELALUI SOFTWARE PENGETIKAN BERMANUSKRIP BAHASA INDONESIA - Setyawardani, Maya; Raharso, Sri; Tjahyawati, Sri Suryani (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2016)
This research aims to identify the performance of keyboarding skill needed by various industries in West Java and surrounding areas. After that, based on the results of the identification, researchers develop keyboarding skills learning modules based on software Mavis Beacon. In addition, the study also stimulate students to create manuscripts that will be imported into the Indonesian Language software Mavis Beacon and used to practice typing. Based on the results of a survey of employees in the daily use of computers as tools of work, is to have an average typing speed 35 words/minute. Furthermore, the researchers successfully created keyboarding skills learning modules, the modules are equipped with SAP and GBPP as well as a set of manuscripts that can be imported into the software Mavis Beacon. Lastly, efforts are being made to make manuscripts manuscript group of Indonesian Language is  to give a positive impact against the achievement of performance mastery of keyboarding. This group has an average typing speed for a better (and significant) compared to groups that study without using the Indonesian Language manuscripts.